IL-4 and IL-10 antagonize IL-12-mediated protection against acute vaccinia virus infection with a limited role of IFN-gamma and nitric oxide synthetase 2. - van Den Broek, M; Bachmann, M; Köhler, G; Barner, M; Escher, R; Zinkernagel, R; Kopf, M (2000)
Resistance or susceptibility to most infectious diseases is strongly determined by the balance of type 1 vs type 2 cytokines produced during infection. However, for viruses, this scheme may be applicable only to infections with some cytopathic viruses, where IFN-gamma is considered as mandatory for host defense with little if any participation of type 2 responses. We studied the role of signature Th1 (IL-12, IFN-gamma) and Th2 (IL-4, IL-10) cytokines for immune responses against vaccinia virus (VV). IL-12-/- mice were far more susceptible than IFN-gamma-/- mice, and primary CTL responses against VV were absent in IL-12-/- mice but remained intact in IFN-gamma-/- mice. Both CD4+ and CD8+ T cells from IL-12-/- mice were unimpaired in IFN-gamma production, although CD4+ T cells showed elevated Th2 cytokine responses. Virus replication was impaired in IL-4-/- mice and, even more strikingly, in IL-10-/- mice, which both produced elevated levels of the proinflammatory cytokines IL-1alpha and IL-6. Thus, IL-4 produced by Th2 cells and IL-10 produced by Th2 cells and probably also by macrophages counteract efficient anti-viral host defense. Surprisingly, NO production, which is considered as a major type 1 effector pathway inhibited by type 2 cytokines, appears to play a limited role against VV, because NO sythetase 2-deficient mice did not show increased viral replication. Thus, our results identify a new role for IL-12 in defense beyond the induction of IFN-gamma and show that IL-4 and IL-10 modulate host protective responses to VV.